B. F. Stern correspondence - Stern, B. F.
ALS written by Stern to John M. Broomall relating to politics during Reconstruction and the presidential administration of Andrew Johnson.
Public official in the U.S. Treasury Dept.
Collection material in English.
Forms part of: Miscellaneous Manuscripts collection.
Keywords: Broomall, John M. -- 1816-1894 -- Correspondence; Johnson, Andrew, -- 1808-1875.; Reconstruction (U.S. history, 1865-1877); United States -- Politics and government -- 1865-1869.; Public officials